Genome‐Wide Association Study of Dermatomyositis Reveals Genetic Overlap With Other Autoimmune Disorders1. Issue 12 (December 2013) - Miller, Frederick W.; Cooper, Robert G.; Vencovský, Jiří; Rider, Lisa G.; Danko, Katalin; Wedderburn, Lucy R.; Lundberg, Ingrid E.; Pachman, Lauren M.; Reed, Ann M.; Ytterberg, Steven R.; Padyukov, Leonid; Selva‐O'Callaghan, Albert; et al.
<x xml:space="preserve">Abstract</x> Objective To identify new genetic associations with juvenile and adult dermatomyositis (DM). Methods We performed a genome‐wide association study (GWAS) of adult and juvenile DM patients of European ancestry (n = 1, 178) and controls (n = 4, 724). To assess genetic overlap with other autoimmune disorders, we examined whether 141 single‐nucleotide polymorphisms (SNPs) outside the major histocompatibility complex (MHC) locus, and previously associated with autoimmune diseases, predispose to DM. Results Compared to controls, patients with DM had a strong signal in the MHC region consisting of GWAS‐level significance (P < 5 × 10–8) at 80 genotyped SNPs. An analysis of 141 non‐MHC SNPs previously associated with autoimmune diseases showed that 3 SNPs linked with 3 genes were associated with DM, with a false discovery rate (FDR) of <0.05. These genes were phospholipase C–like 1 (PLCL1; rs6738825, FDR = 0.00089), B lymphoid tyrosine kinase (BLK; rs2736340, FDR = 0.0031), and chemokine (C‐C motif) ligand 21 (CCL21; rs951005, FDR = 0.0076). None of these genes was previously reported to be associated with DM. Conclusion Our findings confirm the MHC as the major genetic region associated with DM and indicate that DM shares non‐MHC genetic features with other autoimmune diseases, suggesting the presence of additional novel risk loci. This first identification of autoimmune disease genetic predispositions shared with DM may lead to enhanced understanding of pathogenesis and novel diagnostic and therapeutic approaches.